Modern international protection of children’s rights - Гнатюк, Тетяна Миколаївна (My University, 2020)
Human rights are an inalienable right of everyone from birth. Respect for human rights and freedoms is seen as an indicator of the development of society. The Convention on the Rights of the Child, adopted in 1989 by the UN General Assembly and entered into force a year later, profoundly changed the world treatment of children. Like the Universal Declaration of Human Rights, the Convention formulated something fundamental to human well-being and acted as a watershed and a guide for future generations. According to the provisions of the Convention, the child is an active member of the family, community and society. The announcement of the Global Movement for Children in 1999 marked the beginning of major changes. All over the world, the movement aims to unite all those who believe that children's rights should be a priority. One of the main goals of the movement is to provide a clear understanding that the world's citizens care for children and expect governments to keep their promises.
Keywords: Child; children's rights; international protection of children's rights; human rights; system of protection of children's rights